Pendidikan Seks Bagi Remaja Menurut Abdullah Nasih Ulwan - Saputra, Muhammad Indra (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2016)
Reproductive health, in this case, is the Sex and the problem is difficult to solve. During this time people view sex as "taboo" and inappropriate to talk about. In this case, that sex should not be taboo, but sexual problems should be presented to children and adolescents in strict accordance with the guidance of the Shari'ah. Adolescence in the developmental process is a period that is very prone to moral development,  both physically  and socially.  For those  who are  weak beliefs  or moral principles which have less, often leads to destructive and immoral.In connection  with the  trend of  promiscuity adolescents,  reproductive health problems are not be underestimated. The solution is to give an explanation regarding reproductive  or sexual  health information  that is  positive for  young people with reproductive  or sexual  health education  in  Islamic.  In this  case, the authors are interested  to further  investigate the  Nasih  Ulwan  Abdullah thinking about the concept of Sex Education For Teens.